Ausspracheabweichungen im Hochdeutsch thailändischer Immigrantinnen in der Deutschschweiz - Attaviriyanupap, Korakoch (Linguistik Online, 2006)
The situations of Thais not being understood by German native speakers even though they use correct words have always been experienced. However, the pronunciation difficulties of Thai native speakers are mostly just taken for granted as typical errors, but not systematically listed and discussed. As found out in the corpus consisting of utterances in Standard German of 16 female immigrants living in German-speaking Switzerland, their pronunciation variations which differ from the norm of the target language are very systematic and predictable because they are based on Thai sound patterns. This article aims to present a contrastive analysis of German and Thai in terms of segmental elements and syllable structure and to give an overview of systematic nontarget-like pronuncation of German second language learners who are native speakers of Thai. The findings should be made useful in teaching German as second language to this group of learners.